Diseño de una planta de tratamiento de aguas residuales del camal municipal de pedro Vicente Maldonado - Zurita Malliquinga, Emma Verónica (2015)
This research was made at Pedro Vicente Maldonado Municipal Slaughter house, the objective to propose a treatment plant design for wastewater. in the diagnosis of the object under study, it was determined that the slaughterhouse has an oxidation pool, whose efficiency is negative, as it presents fluent infiltration problems, therefore it is poured directly into the public sewer system, so it was necessary to focus on wastewater laboratory analysis then the analysis, data results had to be compared with parameters of TULSMA environmental regulations,: total coliforms and fecal coliforms exceeded the permissible limit range (600 mg / L and 3000 mg / l), there is biological pollution: BOD 5 shows an increase of 423.6%, exceeds the allowable limit range (250 mg / l) and the result of the analysis is 1059 mg / l; Likewise the COD parameter shows an increase of 250%, exceeds the allowable limit range (500 mg / l), and the analysis results have 1250 mg / l; The total solids exceeds the allowable limit range (1600 mg / l), and the analysis results have 9324 mg / l....